Material didáctico a base de objetos reciclados para el desarrollo de la motricidad fina en los niños de educación inicial 2 en la Unidad Educativa Manuel Gonzalo Albán Rumazo del sector de Alaquez de la ciudad de Latacunga - Jaya Lema, Enma Diocelina (2023)
The present investigation focuses on the development of fine motor skills in children of initial education taking into account that at present it has a transcendental importance because through which it allows children to develop skills, motor skills in their body, mainly with their hands. acquiring security, self-confidence, that is to say that as a problem we have the deficiency of fine motor skills in children of initial education 2 of the Educational Unit "Manuel Gonzalo Albán Rumazo" for which a guide of didactic material has been designed based on of recycled objects which contains ten didactic activities that help to strengthen fine motor skills in children. The methodology used in this research is a mixed quanti approach. qualitative, with field modality using the inductive method.